Effect of Pigment Intensity and Region of Eggshell on the Spectral Transmission of Light That Passes the Eggshell of Chickens - Shafey, T.M.; Ghannam, M.M.; Al-Batshan, H.A.; Al-Ayed, M.S. (International Journal of Poultry Science, 2004)
The effects of intensity of brown pigment and region (small pole, equator and large pole) of eggshell on eggshell thickness and per cent transmittance of light (PT) that passes through the eggshell of chicken eggs were investigated. The PT was measured over the wavelength (WL) range of 200 to 800 nm (near-ultra violet (near-UV) WL range from 200 to 380 nm, visible (V) WL range from 380 to 780 nm and near-infra red (near-IR) WL range from 780 to 800 nm). Brown pigment eggshells [light (LBP), medium (MBP) and dark (DBP)] from meat-type breeder (Hybro) eggs of comparable weight were used. The intensity of brown pigment and region of eggshells did not affect eggshell thickness, but significantly (P